Effect of nutrition intervention coupled with healthy dietary advice on the nutritional status of pregnant women in the northern zone of the Sidama region, Ethiopia: a multilevel, cluster randomized controlled trial - Kaleb Mayisso; Tafese Bosha; Dessalegn Tamiru (Journal of Health, Population and Nutrition)
Abstract Background Pregnant women with poor nutritional status, as indicated by a low body mass index, short stature, and micronutrient deficiencies, are at greater risk of poor birth outcomes. Thus, this study aimed to assess the effects of an egg-based diet intervention coupled with healthy dietary advice on nutritional status among pregnant women in the northern zone of the Sidama region, Ethiopia. Methods A community-based, multilevel, cluster-randomized controlled trial was employed. A total of 318 pregnant women were included in the study. An egg-based diet and healthy dietary advice were provided to the intervention group, whereas standard healthcare was given to the control group. The baseline and end-line nutrient adequacy and nutritional status were measured via standard questions. A linear mixed-effects model was fitted to evaluate the effects of the intervention on nutrient adequacy and nutritional status, accounting for the clustering effect. Results There was a significant difference in the mean difference in the MUAC (1.634 ± 1.07 cm) between baseline and the end line between the study subjects in the intervention group (p value = 0.001), but no significant difference was observed in the mean difference of MUAC (0.032 ± 0.209 cm) among the control group at baseline and the end line (p > 0.05). The multivariable linear mixed model revealed that having received nutrition intervention was positively associated with mid-upper arm circumference (β = 0.54, 95% CI 0.281, 0.782, p value < 0.001) and the mean adequacy ratio (β = 344.019, 95% CI 275.965, 412.073, p value < 0.001) at the end line. Conclusion The evidence from this study indicated that egg intake is an important protein source and provides several key nutrients, including vitamins A and D, folate, iron, and calcium. Thus, it is important to demonstrate the nutritional benefits of egg consumption during pregnancy. Healthcare professionals should be aware of this information, contextualize it, and communicate it to family heads and the community to help alleviate the restricted consumption of eggs during pregnancy. Trial registration The protocol for this study was registered at https://clinicaltrials.gov/with the registration number NCT06521151 on 07/22/2024.